Biofuels and bioenergy : processes and technologies - Lee, Sunggyu; Shah, Yatish T. (Boca Raton, FL : Taylor & Francis, 2012)
'Preface Humans have a long history of using a wide variety of biomass resources as sources of energy and fuel. The discovery and use of fossil energy, represented largely by coal, natural gas, and petroleum, have drastically reduced the utilization of biomass fuels. The technologies of generating electricity using biomass, producing bioliquid fuels, and powering motor vehicles using bioalcohols and blended gasolines have been developed and practiced since the early twentieth century. Up until recently, however, development interest in biofuels had lessened due to the availability of relatively inexpensive fossil energy resources as well as the handling and transportation convenience of these conventional fuel sources. Due to the strong growth of global transportation fuel demand, sharply escalating worldwide fossil energy prices, fear over the dwindling supply of petroleum and natural gas for the near future, and credible evidence linking global warming and climate change issues with the emission of greenhouse gases, global interest and R&D efforts in renewable alternative fuels have become intense and fiercely competitive, targeting both short- and long-term solutions to alternative energy needs. Although there are a number of options and routes for energy sustainability and independence via renewable alternative energy, bioenergy and biofuels certainly possess outstanding potential to provide solutions and relief to many of the immediate, intermediate, and long-term societal needs of clean energy and their associated challenges'--
Includes bibliographical references and index.
Keywords: Biomass energy